2018
DOI: 10.1590/0104-070720180003780016
|View full text |Cite
|
Sign up to set email alerts
|

Comparação Entre Gravidade Do Paciente E Carga De Trabalho De Enfermagem Antes E Após a Ocorrência De Eventos Adversos Em Idosos Em Cuidados Críticos

Abstract: RESUMO Objetivo: comparar a gravidade do paciente e a carga de trabalho de enfermagem antes e após a ocorrência de evento adverso moderado e grave em idosos internados em unidades de terapia intensiva. Método: estudo comparativo, realizado em nove unidades de terapia intensiva de um Hospital Universitário de São Paulo. Os eventos foram coletados dos prontuários dos pacientes e classificados em moderados e graves segundo a Organização Mundial de Saúde. A análise da gravidade foi realizada segundo o Symplified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
1
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 28 publications
0
3
1
6
Order By: Relevance
“…The mean workload values of 52.91 points (12.7 hours of nursing care) observed in our study were lower than in various studies (Ortega, D'Innocenzo, Silva, & Bohomol, 2017;Toffoletto, Oliveira, Andolhe, Barbosa, & Padilha, 2018;Oliveira et al, 2015;Bruyneel et al, 2019;Lucchini et al, 2019). This mean was lower than other ICUs evaluated from the same institution, being this the general adult, neonatal II, neonatal III and pediatric ICUs (Mendes-Rodrigues et al, 2017-b).…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…The mean workload values of 52.91 points (12.7 hours of nursing care) observed in our study were lower than in various studies (Ortega, D'Innocenzo, Silva, & Bohomol, 2017;Toffoletto, Oliveira, Andolhe, Barbosa, & Padilha, 2018;Oliveira et al, 2015;Bruyneel et al, 2019;Lucchini et al, 2019). This mean was lower than other ICUs evaluated from the same institution, being this the general adult, neonatal II, neonatal III and pediatric ICUs (Mendes-Rodrigues et al, 2017-b).…”
Section: Discussioncontrasting
confidence: 69%
“…Mean NAS of 73.40 points was found in a trauma ICU in São Paulo, with a minimum of 35.00 points and a maximum of 123.00 points (Padilha et al, 2017). In another study, the mean NAS found was 74.27 points in patients' victims of adverse events hospitalized in nine ICUs in the city of Sao Paulo, and those who did not suffer adverse events had a mean NAS of 71.20 (Toffoletto, Oliveira, Andolhe, Barbosa, & Padilha, 2018).…”
Section: Discussionmentioning
confidence: 91%
“…13 The absence of a member of the nursing team has a negative impact, as it generates more work for those present, effects work organization, demotivates employees who are relocated to the service, decreases the quality of care provided to patients and favors the occurrence of adverse events. [18][19][20] In addition, this situation contributes to the development of physical and mental disorders in workers. Consequently, a cascade of problems arises, such as illness and increased absenteeism.…”
Section: Discussionmentioning
confidence: 99%
“…Os diferentes autores definem a CT de enfermagem como sendo o trabalho que se relaciona diretamente ao paciente e as atividades administrativas. Essa carga é calculada a partir do tempo necessário para realizar o trabalho de enfermagem em um período determinado, além do número médio de pacientes atendidos de acordo com a dependência e tipo de cuidados, multiplicado pelo tempo médio de assistência em horas 3 .…”
Section: Introductionunclassified